2016
DOI: 10.1002/2015gc006236
|View full text |Cite
|
Sign up to set email alerts
|

Mass transfer in the lower crust: Evidence for incipient melt assisted flow along grain boundaries in the deep arc granulites of Fiordland, New Zealand

Abstract: Knowledge of mass transfer is critical in improving our understanding of crustal evolution, however mass transfer mechanisms are debated, especially in arc environments. The Pembroke Granulite is a gabbroic gneiss, passively exhumed from depths of >45 km from the arc root of Fiordland, New Zealand. Here, enstatite and diopside grains are replaced by coronas of pargasite and quartz, which may be asymmetric, recording hydration of the gabbroic gneiss. The coronas contain microstructures indicative of the former … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 133 publications
(162 reference statements)
2
40
0
Order By: Relevance
“…Relict igneous pyroxene is variably replaced by a hydrous assemblage of coronitic blue–green pargasite and quartz symplectite. The symplectite minerals show no evidence of internal deformation or recrystallization, and have been interpreted to have formed under static conditions post‐D 1 due to melt–rock interaction during diffuse porous melt flow along grain boundaries (Stuart et al ., ). The GRZ form during a second melt–rock interaction event where garnet pseudomorphs coronitic pargasite.…”
Section: Discussionmentioning
confidence: 99%
“…Relict igneous pyroxene is variably replaced by a hydrous assemblage of coronitic blue–green pargasite and quartz symplectite. The symplectite minerals show no evidence of internal deformation or recrystallization, and have been interpreted to have formed under static conditions post‐D 1 due to melt–rock interaction during diffuse porous melt flow along grain boundaries (Stuart et al ., ). The GRZ form during a second melt–rock interaction event where garnet pseudomorphs coronitic pargasite.…”
Section: Discussionmentioning
confidence: 99%
“…The Pembroke Granulite, Fiordland, New Zealand (Figure ), is a relatively low‐strain portion of the Median Batholith (Figure , inset), a composite regional batholith comprising Carboniferous to Early Cretaceous plutons from the lower crust of a Cordilleran magmatic arc (Blattner, ; Mortimer et al., ). The gabbroic protolith to the Pembroke Granulite was emplaced at 136–129 Ma (Hollis, Clarke, Klepeis, Daczko, & Ireland, ; Stowell, Tulloch, Zuluaga, & Koenig, ) and had an igneous assemblage of enstatite, diopside, brown‐green pargasite, plagioclase, and ilmenite (Stuart, Piazolo, & Daczko, ). Though commonly gabbroic, the whole rock composition of the protolith varies by several weight percent for all major element oxides and has some minor grain size variations (Stuart et al., ).…”
Section: Regional Geologymentioning
confidence: 99%
“…The gabbroic protolith to the Pembroke Granulite was emplaced at 136–129 Ma (Hollis, Clarke, Klepeis, Daczko, & Ireland, ; Stowell, Tulloch, Zuluaga, & Koenig, ) and had an igneous assemblage of enstatite, diopside, brown‐green pargasite, plagioclase, and ilmenite (Stuart, Piazolo, & Daczko, ). Though commonly gabbroic, the whole rock composition of the protolith varies by several weight percent for all major element oxides and has some minor grain size variations (Stuart et al., ). The igneous assemblage was partially recrystallized during D 1 , forming a gneissic foliation (S 1 ) striking generally NE and dipping steeply to the north and south.…”
Section: Regional Geologymentioning
confidence: 99%
“…Exposed roots of volcanic arcs, such as the Kohistan palaeo-island arc, Pakistan (Bouilhol et al 2015), Talkeetna, Alaska (Greene et al 2006), Fjordland, New Zealand (Stuart et al 2016) and exposed ultramafic complexes, Alaska (Murray 1972;Irvine 1974) allow for direct observations of the lower crust, and provide an analogue to Martinique plutonic xenoliths. In Kohistan, kilometre scale magmatic conduits are present in the lower crust, which melt rose through and reacted with the existing cumulate assemblages (Bouilhol et al 2015).…”
Section: Open System Processesmentioning
confidence: 99%
“…McBirney and Noyes 1979;Morse 1996), or in an open system involving the input of percolating reactive melts or liquids (Reiners 1998;Coogan et al 2000Coogan et al , 2001Meurer and Claeson 2002;Leuthold et al 2014;Smith 2014;Bouilhol et al 2015;Stuart et al 2016). It has been shown that the products of reactive liquid flow will differ from one produced by simple crystallisation along a liquid line of descent (Reiners 1998) and the addition of low degree melts cause large variations in incompatible trace elements.…”
Section: VImentioning
confidence: 99%